Mechanisms of Action of Carbapenem Resistance - Caterina Aurilio; Pasquale Sansone; Manlio Barbarisi; Vincenzo Pota; Luca Gregorio Giaccari; Francesco Coppolino; Alfonso Barbarisi; Maria Beatrice Passavanti; Maria Caterina Pace (Antibiotics, 2022)
Carbapenem antibiotics are the most effective antimicrobials for the treatment of infections caused by the most resistant bacteria. They belong to the category of β-lactams that include the penicillins, cephalosporins, monobactams and carbapenems. This class of antimicrobials has a broader spectrum of activity than most other beta-lactams antibiotics and are the most effective against Gram-positive and Gram-negative bacteria. All β-lactams antibiotics have a similar molecular structure: the carbapenems together with the β-lactams. This combination gives an extraordinary stability to the molecule against the enzymes inactivating the β-lactams. They are safe to use and therefore widespread use in many countries has given rise to carbapenem resistance which is a major global public health problem. The carbapenem resistance in some species is intrinsic and consists of the capacity to resist the action of antibiotics with several mechanisms: for the absence of a specific target, or an intrinsic difference in the composition of cytoplasmatic membrane or the inability to cross the outer membrane. In addition to intrinsic resistance, bacteria can develop resistance to antibiotics with several mechanisms that can be gathered in three main groups. The first group includes antibiotics with poor penetration into the outer membrane of bacterium or antibiotic efflux. The second includes bacteria that modify the target of the antibiotics through genetic mutations or post-translational modification of the target. The third includes bacteria that act with enzyme-catalyzed modification and this is due to the production of beta-lactamases, that are able to inactivate carbapenems and so called carbapenemases. In this review, we focus on the mode of action of carbapenem and the mechanisms of carbapenem resistance.